GREEN EDUCATION GUNA MENUMBUHKAN JIWA WIRAUSAHA SEJAK DINIBERBASIS BUSINESS MODEL CANVAS DI SEKOLAH ALTERNATIF “TEMBASALEKO”KOTABIMA - APRIANTI, KARTIN; PRATIWI, ALIAH; MULYATI, MULYATI; SULISTIANINGSIH, SULISTIANINGSIH; ANANTA, ASTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
The partner of this community empowerment program for beginners (PMP) is the alternative school “Temba Saleko”. In addition to the main learning activities, the alternative school “Temba Saleko” is committed to developing children into creative and innovative individuals while still paying attention to environmental preservation. Based on the results of field visits and interviews, several problems faced by partners related to their students can be identified, namely: a) children's awareness and knowledge of environmental preservation is still low; b) low interest in entrepreneurship; and c) limited human resources who understand the business model canvas as a tool for developing creative ideas. The objectives and targets of this PMP are: a) fostering a proactive and adaptive attitude towards environmental problems; b) instilling and fostering an entrepreneurial spirit from an early age that supports green education and green economy; and c) making the business model canvas a tool for expressing creative ideas. Through the PMP grant program, the PMP team together with partners carry out various activities, including green education socialization, educational visits to the Main Waste Bank of Bima City, entrepreneurship seminars, and business model canvas training aimed at instilling an entrepreneurial spirit that supports green education and green economy from an early age. Based on the evaluation results, the PMP program showed an increase of 91.7% in knowledge, attitudes, and skills, and 97.9% of participants strongly agreed with the positive impact of the activities that had been implemented. From the activities that had been implemented, the PMP team produced several program products, including crafts from used plastic bottles, green education e-modules, waste sorting project e-modules, Kidspreneur green entrepreneurship e-modules, Kidspreneur-Project Model Canvas e-modules My Business, animated video